COMPARISON OF MACULAR THICKNESS BETWEEN HIGHLY MYOPIC AND NORMAL CHILDREN AGED 5 TO 8 YEARS USING OPTICAL COHERENCE TOMOGRAPHY - Sultan, Maria; Hamza, Syed Amir; Ali Shah, Mir; Naeem Khan, Mohammad; Saeed, Nasir (Journal of Postgraduate Medical Institute, 2018)
Objective: To compare of macular thickness between highly myopic and nor- mal children aged 5 to 8 years using optical coherence tomography. Methodology: A prospective case control comparative study was performed in the Department of Ophthalmology, Hayatabad Medical Complex, Peshawar from July 2015 to June 2016. Children meeting the inclusion criteria of both genders were selected from outpatient department using non-probability pur- posive sampling after complete ophthalmological examination. Children aged 5 to 8 years were divided in two groups. Group1: high myopic children (>-6.00 D) and Group 2: healthy age matched controls (-1 to +2 D). Optical coherence tomography (OCT) macula was performed on children in both groups, measur- ing average thicknesses of the fovea (central 1 mm), inner (1 to 3 mm) and outer parafoveal area (3 to 6 mm), in all the four quadrants. Calculations were also done for total volume of scanned macular area. The macular thickness of these two groups was compared and Mann–Whitney U test (two tailed test, unpaired/ independent) was used to calculate the differences between the two groups. Results: There were 25 patients in high myopic group and 25 patients in control group. Thickness of 1mm central foveal ring was significantly greater in children included in high myopia group. The parafoveal thickness was significantly thin- ner in all four quadrants of inner and outer circles in high myopia group. The calculated macular volume (average) of the highly myopic children was signifi- cantly smaller as compared to control group. Conclusions: There was thicker fovea, thinner parafoveal macular area and smaller macular volume in children having high myopia aged 5 to 8 years as compared to age matched healthy controls.